Relation of Sensory Peripheral Neuropathy in Sjögren Syndrome to anti-Ro/SSA - Scofield, Amanda K. (2012)
BACKGROUND: Sjögren syndrome is a common, chronic autoimmune disease that typically produces inflammation and poor function of the salivary and lacrimal glands. Other organs can be affected, including the nervous system. Sensory peripheral neuropathy is a common manifestation of the disease. METHODS: Eight-eight patients attending a dry eyes-dry mouth clinic were classified as primary Sjögren syndrome and underwent a neurological examination. Anti-Ro (or SSA) and anti-La (or SSB) were determined using immunodiffusion as well as Inno-Lia and BioPlex ANA screen. Serum vitamin B12 levels were determined using an enzyme-linked microtiter plate assay. RESULTS: Twenty-seven (31%) of the 88 patients had peripheral neuropathy as defined by loss of light touch, proprioception or vibratory sensation. Anti-Ro and anti-La were found by immunodiffusion in 12 patients, and 8 of these 12 had neuropathy (χ(2)=8.46, p=0.0036, odds ratio = 6.0 compared to those without precipitating anti-Ro and anti-La). Of the 27 patients with only anti-Ro by immunodiffusion, 13 (48.1%) of these had neuropathy (χ(2) =5.587, p=0.018 compared to those without anti-Ro). There was no relationship of the other, more sensitive measures of anti-Ro and anti-La to neuropathy. In addition, we found no association of serum vitamin B12 levels to neuropathy among these patients with Sjögren syndrome. CONCLUSION: Sensory peripheral neuropathy is common among patients with Sjögren syndrome, and is associated with the presence of anti-Ro and anti-La when determined by immunodiffusion.